Seasonal differences in future climate and streamflow variation in a watershed of Northern China - Wenxu Cao (Elsevier, 2021)
Study region: The Chaohe watershed is a meso-scale watershed in northern China, and the primary reservoir watershed for Beijing's drinking water supply. Study focus: This research aims to evaluate the effects of climate change on future seasonal streamflow regimes and understand the challenges to watershed management. The Regional Hydro-Ecological Simulation System (RHESSys) was applied to investigate the watershed's future hydrographic characteristics under the forcing of the downscaled precipitation and temperature projected by General Circulation Models (GCMs) under three emissions scenarios. New hydrological insights for the region: The future climate exhibits a drier and warmer trend in the summer monsoon period contrasting with other seasons in the watershed. Precipitation will decrease by 47.5–57.2 mm during the summer monsoon period while increasing annually. Future summer streamflow will decrease accordingly, which is also driven by increased evapotranspiration due to rising temperature. An increased dispersion coefficient of streamflow also indicates more dramatic variations in summer. The annual streamflow magnitude with a 5-year return period increases significantly (p < 0.01), indicating a reduced risk for future water shortages. However, the magnitude of streamflow will decrease with the prolonged return periods (p < 0.01). This study emphasizes the critical significance of predicting the seasonal variability of streamflow and other hydrological property changes at the local scale to provide valuable information for developing adaptive resource management and hazard relief strategies.